Contribution of leg flexibility, limb length, leg power for the split leap skills of rhythmic gymnastics athletes - Aji-Putra, R. B.; Soenyoto, T.; Darmawan, A.; Irsyada, R. (International Journal of Human Movement and Sports Sciences, 2021)
This study examined the association between leg flexibility, leg length, jump height, and split leap movement scores at various levels of rhythmic gymnasts. Fifty-two young rhythmic gymnasts (age: 10.63 ± 2.9 years) were divided into two groups (qualifying, n = 32 and non-qualifying, n = 20) based on age and regional championship level. The gymnast underwent a series of fitness tests in the form of leg flexibility and leg explosive power as well as a split jump performance which was judged by 2 national and international certified judges. There was a significant difference and correlation between qualification and non-qualification in the split leap score (p = 0.00), body weight (p = 0.00; r = 0.351), limb length (p = 0.00; r = 0.420), High Jump (p = 0.01; r = 0.279), raised straight legs (p = 0.021; r = -0.279). There was no difference found in point feet but positively related at split leap score (p = 0.386; r = 0.373). The overall multiple regression analysis of all novice athletes revealed that Limb length, point feet, and high jump accounted for a medium part (32%) of the split leap score. In conclusion, the level of the gymnast (non-qualification), weight, Limb length, and arm length had a greater effect on the implementation of the split leap, whereas at the junior level (qualification) the leg explosiveness and flexibility of the leg effectively contributed to the split leap movement. Overall, the athlete's flexibility, body composition, and the explosive power of the limb variables effectively contribute to the split leap movement in youth rhythmic gymnastics.